2006
DOI: 10.1007/bf03161184
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular ophthalmic homatropine vs. atropine to prevent lethality in rates with dichlorvos poisoning

Abstract: Introduction: Most hospitals lack a sufficient supply of atropine to treat, simultaneously, patients poisoned with multiple organophosphorous compound (OC) or nerve agent. The presence of a ubiquitous alternate antidote would prove useful if mass poisoning occurred. Our objective was to evaluate the effect of ophthalmic homatropine (Isopto Homatropine 5%) on survivability in a rat model of significant, acute OC poisoning.Methods: Sprague-Dawley rats were randomized to one of five pre-treatment groups (N = 10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The cardinal treatment for organophosphate poisoning includes atropine to counteract the muscarinic signs and symptoms, and oximes to reactivate the inhibited cholinesterases [ 4 , 16 , 26 , 28 ]. However, the clinical results of administering antidotal therapy for organophosphate poisoning are far from perfect [ 4 , 6 , 16 , 26 , 28 ], and there are many ongoing experimental trials using other therapeutic and protective agents for controlling the signs and symptoms of poisoning, and especially those related to the nicotinic effects that are not controlled by atropine. Examples of such trials include antihistamine diphenhydramine [ 5 , 12 ], alpha-2-adrenoceptor agonists [ 7 , 29 ] and metoclopramide, which is a dopamine D2 receptor antagonist [ 14 , 22 - 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cardinal treatment for organophosphate poisoning includes atropine to counteract the muscarinic signs and symptoms, and oximes to reactivate the inhibited cholinesterases [ 4 , 16 , 26 , 28 ]. However, the clinical results of administering antidotal therapy for organophosphate poisoning are far from perfect [ 4 , 6 , 16 , 26 , 28 ], and there are many ongoing experimental trials using other therapeutic and protective agents for controlling the signs and symptoms of poisoning, and especially those related to the nicotinic effects that are not controlled by atropine. Examples of such trials include antihistamine diphenhydramine [ 5 , 12 ], alpha-2-adrenoceptor agonists [ 7 , 29 ] and metoclopramide, which is a dopamine D2 receptor antagonist [ 14 , 22 - 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 In choosing a dose of homatropine for study, we found that doubling the dose of homatropine (20 mg/kg vs. 10 mg/kg of atropine sulfate) was equivalent to standard atropine sulfate in preventing death in our previous work in the laboratory as well as in this current experiment. 8 Our study revealed a significant survival benefit for rats treated with standard atropine sulfate (10 mg/kg), ophthalmic homatropine (20 mg/kg), and ophthalmic atropine sulfate (10 mg/kg). All subjects consistently exhibited fasciculations within 2-3 minutes of dichlorvos administration.…”
Section: Discussionmentioning
confidence: 59%
“…8 Before ophthalmic antidote testing, 30 animals were used to obtain an appropriate dose response. It was discovered that administration of dichlorvos (Pestanal; Sigma-Aldrich) subcutaneously (SC; 10 mg/kg) resulted in death within 7 minutes in 10 rats.…”
Section: Study Protocolmentioning
confidence: 99%
“…Our previous work determined that reported LD50 values for dichlorvos and atropine dosing that were used in published studies were not adequate in our laboratory and thus necessitated a dose response phase before experimentation. 8 Before ophthalmic antidote testing, 30 animals were used to obtain an appropriate dose response. It was discovered that administration of dichlorvos (Pestanal; Sigma-Aldrich) subcutaneously (SC; 10 mg/kg) resulted in death within 7 minutes in 10 rats.…”
Section: Study Protocolmentioning
confidence: 99%